Encyclopedia of Life Sciences 2017
DOI: 10.1002/9780470015902.a0027365
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic RNA Decay

Abstract: RNA (ribonucleic acid) molecules play vital roles in the eukaryotic cells, not only as mediators of the flow of genetic information from DNA (deoxyribonucleic acid) to proteins but also as potent regulators of gene expression in general. Ubiquitous transcription of the eukaryotic genome, occurring in the cell nucleus, leads to the synthesis of multiple precursor RNA molecules, which undergo class‐dependent, very often complex processing events, eventually generating mature transcripts, such as mRNAs, tRNAs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…The planetesimal mass per AU in the 5-10 AU region could in principle have been one to two orders of magnitude higher than what is inferred from interior and exterior regions, perhaps as the result of planetesimal formation by pebble pile-ups exterior of the water ice line (Drażkowska, & Dullemond, 2018). However, simulations of the early migration history of Jupiter show that ∼1 M E of planetesimals is scattered in front of Jupiter and parked in the asteroid belt (Raymond & Izidoro, 2017;Pirani et al, 2019), when a standard planetesimal population comparable to that of the minimum mass solar nebula is assumed (Hayashi, 1981).…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…The planetesimal mass per AU in the 5-10 AU region could in principle have been one to two orders of magnitude higher than what is inferred from interior and exterior regions, perhaps as the result of planetesimal formation by pebble pile-ups exterior of the water ice line (Drażkowska, & Dullemond, 2018). However, simulations of the early migration history of Jupiter show that ∼1 M E of planetesimals is scattered in front of Jupiter and parked in the asteroid belt (Raymond & Izidoro, 2017;Pirani et al, 2019), when a standard planetesimal population comparable to that of the minimum mass solar nebula is assumed (Hayashi, 1981).…”
Section: Introductionmentioning
confidence: 78%
“…Lenz et al (2019) showed that the trapping of drifting pebbles in vortices and pressure bumps could form approximately 100 Earth masses of planetesimals, far less than the 1,000 Earth masses needed to drive core growth by planetesimal accretion. Drażkowska, & Dullemond (2018), on the other hand, found that several hundred Earth masses of planetesimals can form from pebble pileups in a relatively narrow region beyond the water-ice line. A large fraction of this population of planetesimals (∼10%) would nevertheless have been pushed into the asteroid belt by the migrating proto-Jupiter (Raymond & Izidoro, 2017;Pirani et al, 2019), indicating that planetesimal formation at the water-ice line cannot have been as efficient in the solar system as found in Drażkowska, & Dullemond (2018).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inside the protosolar nebula, Pluto and other trans-Neptunian objects (TNOs) begin their lives as disparate small particles with a broad range in sizes and (probably) semimajor axes (e.g., Armitage 2013;Birnstiel et al 2016;Lammer & Blanc 2018;Raymond et al 2018). Within a few thousand yr, these particles grow to cm and larger sizes (e.g., Dullemond & Dominik 2005;Brauer et al 2008;Birnstiel et al 2010;Drażkowska & Dullemond 2018;Lenz et al 2019). During the next 0.1-0.3 Myr (e.g., Najita & Kenyon 2014), agglomeration and concentration processes generate km-sized or larger planetesimals (e.g., Youdin & Goodman 2005;Johansen et al 2006Johansen et al , 2007Lambrechts & Johansen 2012;Birnstiel et al 2016;Arakawa & Nakamoto 2016;Blum 2018).…”
Section: Introductionmentioning
confidence: 99%